2012
DOI: 10.1071/ch11424
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of Halo-Substituted Aroylhydrazones with Antimicrobial Activity

Abstract: A series of new halo-substituted aroylhydrazones have been prepared and structurally characterized by elemental analysis, 1H NMR, 13C NMR, and IR spectra, and single crystal X-ray diffraction. The compounds were evaluated for their antibacterial (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas fluorescence) and antifungal (Candida albicans and Aspergillus niger) activities by the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) method. Among the tested compounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(44 citation statements)
references
References 9 publications
0
44
0
Order By: Relevance
“…The shorter distances of the C-N bonds and the longer distances of the C=O bonds for the -C(O)-NH-units than usual, suggests the presence of conjugation effects in the molecules. The remaining bond lengths in the compounds are comparable to each other, and within normal values [17,18]. The dihedral angles between the benzene and pyridine rings are 5.3(3)° for 1, and 4.9(3)° and 1.1(3)° for 2.…”
Section: Chemistrymentioning
confidence: 48%
See 1 more Smart Citation
“…The shorter distances of the C-N bonds and the longer distances of the C=O bonds for the -C(O)-NH-units than usual, suggests the presence of conjugation effects in the molecules. The remaining bond lengths in the compounds are comparable to each other, and within normal values [17,18]. The dihedral angles between the benzene and pyridine rings are 5.3(3)° for 1, and 4.9(3)° and 1.1(3)° for 2.…”
Section: Chemistrymentioning
confidence: 48%
“…Moreover, isonicotinohydrazone compounds usually possess three or more donor atoms, which can readily form complexes with various metal atoms [5][6][7][8][9][10][11][12]. Recently, we found that halido-substituted hydrazones have potential antimicrobial activities [13]. Study on the synthesis and structures of such compounds are important for medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Halide substitute groups are reported to improve the antibacterial activities. [11] In the present work, a novel chlorido-bridged dinuclear manganese(III) complex, [Mn 2 L 2 (μ-Cl)Cl 2 )]·Cl·0.5CH 3 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Fluoro has been considered to be a positive substituent group for the enhancement of biological activities. [10] The number of transition metal complexes of Co(III) and Cu(II) with oxygen and nitrogen donor Schiff base derivatives of 5-fluorosalicylaldehyde is limited. Here we present the synthesis and characterization of new Co(III) and Cu(II) complexes with newly synthesized fluoro-substituted Schiff bases HL 1 and HL 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%